2020
DOI: 10.1007/s00454-020-00192-1
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Graphs, Their Ehrhart Quasi-Polynomials, and a Scissors Congruence Phenomenon

Abstract: The scissors congruence conjecture for the unimodular group is an analogue of Hilbert's third problem, for the equidecomposability of polytopes. Liu and Osserman studied the Ehrhart quasi-polynomials of polytopes naturally associated to graphs whose vertices have degree one or three. In this paper, we prove the scissors congruence conjecture, posed by Haase and McAllister, for this class of polytopes.The key ingredient in the proofs is the nearest neighbor interchange on graphs and a naturally arising piecewis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A better understanding of the connection between Ehrhart equivalence and rational discrete equidecomposability for various classes of polytopes is a fascinating avenue for future research. In particular, the recent work [4] showed that the two notions are equivalent for integral polytopes in R 3 , and the recent work [5] showed the same is true for polytopes associated to cubic graphs.…”
Section: Resultsmentioning
confidence: 96%
“…A better understanding of the connection between Ehrhart equivalence and rational discrete equidecomposability for various classes of polytopes is a fascinating avenue for future research. In particular, the recent work [4] showed that the two notions are equivalent for integral polytopes in R 3 , and the recent work [5] showed the same is true for polytopes associated to cubic graphs.…”
Section: Resultsmentioning
confidence: 96%
“…Although our approach allows us to control the behavior for the difference of polynomials, we were not able, despite many efforts, to find a method to compute the desired polynomials explictly. This seems a challenging task even for {1, 3}-trees as stated in [6,Problem 6.5].…”
Section: Hightlighting Context Of Our Main Resultsmentioning
confidence: 99%
“…Note that a, b, c, and d are not necessarily pairwise distinct. The weight function w , defined as in [6], is such that w f = w f for every f = e and…”
Section: Nearest Neighbor Interchangesmentioning
confidence: 99%
See 2 more Smart Citations